The caldera eaudiobook - Flanagan, John (Brotherband Chronicles, 2017)
The Herons take to the high seas to fend off pirates and rescue the heir to an empire in the newest adventure from John Flanagan, author of the worldwide bestselling Ranger's Apprentice! Includes BONUS content—a brand-new Ranger's Apprentice short story featuring fan-favorites Will and Maddie! In Hallasholm, Stig is contesting the annual Maktig competition to decide Skandia’s greatest warrior. But a late-night knock on the door brings someone Stig never expected to see again, along with a request the Herons are hard-pressed to refuse: a rescue mission of epic proportions. Across the ocean, the southern city-state of Byzantos is plagued by a crew of pirates who’ve kidnapped the son of Empress Justina. Slipping out of Hallasholm under the cover of darkness, the brotherband sets sail to recover the boy from his kidnappers, heading south to the island of Santorillos where a near-impenetrable fortress stands atop a cliff, surrounded by a lagoon—a caldera—formed by the crater of a volcano. In this explosive seventh book in the action-packed Brotherband Chronicles, the Herons battle pirates amid stormy seas as the fate of an empire rests on their shoulders.